Delegating learning - Juan F. Escobar; Qiaoxi Zhang (Theoretical Economics, 2021)
Learning is crucial to organizational decision making but often needs to be delegated. We examine a dynamic delegation problem where a principal decides on a project with uncertain profitability. A biased agent, who is initially as uninformed as the principal, privately learns the profitability over time and communicates to the principal. We formulate learning delegation as a dynamic mechanism design problem and characterize the optimal delegation scheme. We show that private learning gives rise to the tradeoff between how much information to acquire and how promptly it is reflected in the decision. We discuss implications on learning delegation for distinct organizations.
Keywords: D82; D83; 330; Private learning; delegation; delays; deadlines; commitment; cheap talk